ChemInform Abstract: A Review of Experimental Procedures for Heavy Oil Hydrocracking with Dispersed Catalyst. Issue 9 (4th March 2014) - Angeles, M. J.; Leyva, C.; Ancheyta, J.; Ramirez, S.
Abstract Review: 149 refs.